1996
DOI: 10.1007/bf00366925
|View full text |Cite
|
Sign up to set email alerts
|

Climatic factors associated with the infection of herds of cattle with bluetongue viruses

Abstract: The incidence of bluetongue virus infection of 15 cattle herds in Queensland, Australia, was determined by a serum neutralization test. The maximum temperature (degree C), minimum temperature (degree C) and rainfall (mm) data were obtained from the meteorological recording stations closest to each herd. Using unweighted least-squares regression analysis, the best statistical model explaining the most variability in the herd incidence rate included the ratio between the maximum and minimum temperature recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In Australia, seroconversion of sentinel cattle was correlated with Þeld temperatures 1 mo earlier (Ward 1996). However, seroconversion of sentinel cattle in Alabama was not correlated with mean daily temperatures (Wright et al 1993).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In Australia, seroconversion of sentinel cattle was correlated with Þeld temperatures 1 mo earlier (Ward 1996). However, seroconversion of sentinel cattle in Alabama was not correlated with mean daily temperatures (Wright et al 1993).…”
Section: Discussionmentioning
confidence: 95%
“…Bluetongue infection in cattle has been associated with rainfall 1Ð3 mo earlier in Australia (Ward andThurmond 1995, Ward 1996) and total rain days 2 wk earlier in the eastern United States (Wright et al 1993). In southern California, summer rains generally do not occur, and precipitation from June through mid-fall was negligible for each year of this study.…”
Section: Discussionmentioning
confidence: 96%
“…However, the effect of meteorological conditions on BT transmission rate is complex. In Australia, Ward [70] showed that the incidence rate of cattle herds depends on the total monthly rainfall recorded two months before the seroconversion of cattle as well as temperature recorded one month before seroconversion. Moreover, in addition to the crude abundance of Culicoides , their flying activity is important for disease transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia the distributional limits of C. brevitarsis are related to temperature, while rainfall has a stronger effect on summer abundance (130). Several studies in Queensland have successfully related both temperature and rainfall to rates of infection or seroconversion of cattle to BTV (201,203,204).…”
Section: Abundancementioning
confidence: 97%